Positive surgical margins: rate, contributing factors and impact on further treatment: findings from the Prostate Cancer Registry. (14th February 2014) - Evans, Sue M.; Millar, Jeremy L.; Frydenberg, Mark; Murphy, Declan G.; Davis, Ian D.; Spelman, Tim; Bolton, Damien M.; Giles, Graham G.; Dean, Joanne; Costello, Anthony J.; Frauman, Albert G.; Kearns, Paul A.; et al.
<x xml:space="preserve">Abstract</x> Objective To describe the characteristics of patients with and without positive surgical margins (PSMs) and to analyse the impact of PSMs on secondary cancer treatment after radical prostatectomy (RP), with short‐term follow‐up. Patients and Methods We analysed data from 2385 consecutive patients treated using RP, who were notified to the Prostate Cancer Registry by 37 hospitals in Victoria, Australia between August 2008 and February 2012. Independent and multivariate models were constructed to predict the likelihood of PSMs. Independent and multivariate predictors of secondary treatment after RP in the initial 12 months after diagnosis were also assessed. Results Data on PSM status were collected for 2219/2385 (93%) patients. In total 592/2175 (27.2%) RPs resulted in PSMs; 102/534 (19.1%) in the low‐risk group, 317/1218 (26.0%) in the intermediate‐risk group, 153/387 (39.5%) in the high‐risk group, and 9/11 (81.8%) in the very‐high‐risk disease group of patients. Patients having surgery in a hospital where <10 RPs occur each year were significantly more likely to have a PSM (incidence rate ratio [IRR] 1.44, 95% confidence interval [CI] 1.07–1.93) and those in the intermediate‐, high‐ or very‐high‐risk groups (IRR 1.34, 95% CI 1.09–1.65, P = 0.007, IRR 1.96, 95% CI 1.57–2.45, P < 0.001 and IRR 3.81, 95% CI 2.60–5.60, P < 0.001, respectively) were significantly more likely to have a PSM than those in the low‐risk group (IRR 2.50, 95% CI 1.23–5.11, P = 0.012). Patients with PSMs were significantly less likely to have been treated at a private hospital than a public hospital (IRR 0.76, 95% CI 0.63–0.93, P = 0.006) or to have undergone robot‐assisted RP (IRR 0.69, 95% CI 0.55–0.87; P = 0.002) than open RP. Of the 2182 patients who underwent RP in the initial 12 months after diagnosis, 1987 (91.1%) received no subsequent treatment, 123 (5.6%) received radiotherapy, 47 (2.1%) received androgen deprivation therapy (ADT) and 23 (1.1%) received a combination of radiotherapy and ADT. Two patients (0.1%) received chemotherapy combined with another treatment. At a multivariate level, predictors of additional treatment after RP in the initial 12 months included having a PSM compared with a negative surgical margin (odds ratio [OR] 5.61, 95% CI 3.82–8.22, P < 0.001); pT3 compared with pT2 disease (OR 4.72, 95% CI 2.69–8.23, P < 0.001); and having high‐ or very‐high‐risk disease compared with low‐risk disease (OR 4.36, 95% CI 2.24–8.50, P < 0.001 and OR 4.50, 95% CI 1.34–15.17, P = 0.015, respectively). Patient age, hospital location and hospital type were not associated with secondary treatment. Patients undergoing robot‐assisted RP were significantly less likely to receive additional treatment than those receiving open RP (OR 0.59, 95% CI 0.39–0.88, P = 0.010). Conclusions These data indicate an important association between hospital status and PSMs, with patients who underwent RP in private hospitals less likely than those in public hospitals to have a PSM. Patients treated in lower‐volume hospitals were more likely to have a PSM and less likely to receive additional treatment after surgery in the initial 12 months, and robot‐assisted RP was associated with fewer PSMs than was open RP in this non‐randomized observational study. PSM status and pathological T3 disease are both important and independent predictors of secondary cancer treatment for patients undergoing RP. A robot‐assisted RP approach appears to decrease the likelihood of subsequent treatment, when compared with the open approach.